[Bożonarodzeniowa karta okolicznościowa z foto-kolażem] . Christmas greeting card from with a photo-collage (Polska)
B&w print on white paper, with undivided back. Photographic collage. Christmas greeting card contains a photographic collage which represents the Holy Family surrounded by Lech Wałęsa, rev. Jerzy Popiełuszko, John Paul II and [Cardinal Stefan Wyszyński], with mountain landscape in the background.